STRATEGI GURU DALAM MENGATASI KESULITAN MEMBACA AL QURAN DI PPTQ AL IKHLAS - Usamah Habibullah; Hafidz Hafidz (PAI RAFAH, 2023)
This research was conducted to determine the teacher's strategy in dealing with the difficulties experienced by PPTQ Al Ikhlas Sukoharjo students in reading the Al-Qur'an. This research formulates what problems students experience in reading the Koran and how teachers handle these problems. This research aims to find out what problems students experience in reading the Qur'an and how teachers handle these problems. This research study uses a qualitative methodology. This research is included in the classification of field research. The data obtained from this research is through observation, interviews, and documentation. The results of this research show that the strategies applied to overcome difficulties in reading and writing the Al-Qur'an at PPTQ Al Ikhlas, Sukoharjo are, (1) The teacher asks students to read pieces of letters in the Al-Quran one by one. Then, for students who can read it fluently, they are taught to use tones which will later be used in the Al-Quran learning process. (2) In the process of learning to read the Koran, the teacher always gives an example of correct reading and tartil first. Then the teacher asks the students to follow along simultaneously, then the teacher asks or appoints the students one by one to repeat the reading that has been exemplified, and (3) In implementing the process of learning to write the Koran, the teacher writes pieces of verses in the Koran on the blackboard, then the students are asked to write back in their respective notebooks.